European sustainable carriage of goods the role of contract law - Eftestol-Wilhelmsson, Ellen (IMLI studies in international maritime law., 2016)
This work discusses the rapidly developing European transport policy on sustainable freight and the connected efforts initiated by the European Commission (EC) on greening transport by the means of contract law.